Evaluating efficiency and effectiveness in transport organizations - Išoraite, Margarita (Transport, 2005)
The article analyses the following issues: 1. Needs of evaluation. 2. Evaluation techniques and tools. 3. Effectiveness, performance and results. 4. Theoretical views on organizational effectiveness. 5. Transport organizational effectiveness. Transport effectiveness refers to the effectiveness of transport agency’s organizational systems in achieving its internal and external objectives. 6. Effective internal performance systems. 7. A model of transport organizational effectiveness. 8. Efficiency criterion. First Published Online: 27 Oct 2010